Peripheral perfusion index-reference range in healthy Portuguese term newborns - Joana Jardim; Ruben Rocha; Gorett Silva; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2014)
Introduction: Peripheral perfusion index (PPI) is a non-invasive numerical value of peripheral perfusion derived from a pulse oximeter signal. It has been suggested that PPI may be a valuable adjunct diagnostic tool to detect early clinically significant hemodynamic embarrassment. The aim of this paper was to determine normal PPI in healthy newborns, in order to establish cut-off values that can be use in different pathologic settings. Material and Methods: Prospective observational study performed with term newborns, born in a tertiary level care hospital between January 1st to December 31st 2012. Demographic data such as gender, gestational age, birth weight and Apgar score were collected. PPI, heart rate (HR) and arterial blood oxygen saturation (SpO2) were evaluated simultaneous on the right hand (preductal) and on the left foot (postductal) of the newborn, before discharge from the hospital. Results: 2,032 newborns, 52% male, with a mean birth weight of 3,237 ± 432 g and median gestational age of 39 weeks, were evaluated. PPI values obtained were: preductal median of 1.6 with interquartile range of 1.2-2.3, postductal median of 1.4 with interquartile range of 1-2 (p < 0.001). Conclusions: PPI is an easily applicable non invasive method to monitor peripheral perfusion changes. We established normal PPI values in healthy Portuguese newborns. PPI was higher on the upper limb (preductal) when compared to the lower limb (postductal).This finding has important implications, in the time of choosing a single probe placement, and in the interpretation of the results.